Cybersquatting Actions on Domain Name Trademark Rights as the Internet Web - Maulidi, Thoriq Jinan; Sugiri, Bambang; Ruslijanto, Patricia Audrey (Tazir, 2024)
In this ever-evolving digital era, domain names have become a valuable asset for organizations, trademarks and individuals. A domain name is not only an online address, but also an identity that reflects a brand image and facilitates communication and interaction in the internet world. However, the practice of cybersquatting has become a serious threat to trademark owners and the stability of the internet ecosystem. Currently domain names are regulated in articles 23 and 24 of the ITE Law, but these articles do not explain dispute resolution. Then it is also regulated in the MIG Law. This study uses the dogmatic research method and also uses the case approach method, laws and also a comparison of legal systems. The results of this study are that the holder of the rights to the first registering domain name trademark must have a legal protection regulated in Law Number 20 of 2016 concerning Marks and Geographical Indications. Domain name violations related to brands are the duty of PANDI (Indonesian Domain Name Manager). Furthermore, regarding the dispute that occurred above. The parties can resolve it through 2 channels, namely through litigation and also through non-litigation. Where if the parties choose the non-litigation route, it can be done through PPDN (Domain Name Dispute Settlement) formed by PANDI and can also go through arbitration which according to both parties can resolve this dispute properly